2010
DOI: 10.2807/ese.15.34.19644-en
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing outbreak of West Nile virus infections in humans in Greece, July – August 2010

Abstract: Between early July and 22 August 2010, 81 cases of West Nile neuroinvasive disease were reported in the region of Central Macedonia, northern Greece. The median age of cases was 70 years. Encephalitis, meningoencephalitis or aseptic meningitis occurred mainly in patients aged 50 years or older. This is the first time that West Nile virus (WNV) infection has been documented in humans in Greece. Enhanced surveillance and mosquito control measures have been implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
120
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(124 citation statements)
references
References 30 publications
3
120
0
1
Order By: Relevance
“…In the Mediterranean basin, outbreaks of WNV infection in recent years have been reported in France (2004and 2006), Italy (2008, 2009), Morocco (2010, Spain (2010) (www.oie.int/wahis/public.php?page=home) and Greece (Papa et al, 2010). In Portugal, the first evidence of WNV circulation was documented in 1971 when the virus was isolated (Filipe and de Andrade, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…In the Mediterranean basin, outbreaks of WNV infection in recent years have been reported in France (2004and 2006), Italy (2008, 2009), Morocco (2010, Spain (2010) (www.oie.int/wahis/public.php?page=home) and Greece (Papa et al, 2010). In Portugal, the first evidence of WNV circulation was documented in 1971 when the virus was isolated (Filipe and de Andrade, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Papa et al [74] noted that increased rainfall and humidity (together with high temperatures) have probably favoured the multiplication of Culex species, leading to the occurrence of numerous cases of WNV infection in humans in Central Macedonia in summer Table 2. The main climatic change observations (temperature and precipitation) in the study areas and their impacts on WNV transmission.…”
Section: (B) Climate Change Impact On West Nile Virus Transmissionmentioning
confidence: 99%
“…One of the earliest reports of WNV infection occurred in a 12-year-old police horse in Egypt in 1959 (Murgue et al 2002). Since then, WNV outbreaks in humans, birds and horses have been reported in Greece, Hungary, Spain, and central Europe (Papa et al 2010, Kutasi et al 2011, Lopez et al 2011, Bakonyi et al 2013. In sub-Saharan Africa, WNV activity in horses has been documented in Senegal, Côte d'Ivoire, Chad, Democratic Republic of the Congo, Gabon, and Djibouti (Cabre et al 2006), whereas in South Africa, diagnosis and seroprevalence studies of WNV in horses have been reported (Venter et al 2011).…”
mentioning
confidence: 99%